Consensus-Based Single-Phase Control of Three-Phase Inverter for Current Sharing in Three-Phase Four-Wire Isolated AC Microgrids - Rodrigues, Diego T. [UNESP]; Paredes, Helmo K. Morales [UNESP]; Burgos, Claudio; Lima, Rogerio Lucio; Bonaldo, Jakson P. (Institute of Electrical and Electronics Engineers (IEEE), 2022)
This work proposes a novel secondary control system based on the Consensus algorithm to balance the RMS current between the distributed generation (DG) phases in an isolated four-wire Microgrid (MG) containing unbalanced and non-linear loads. The control strategy proposes using a droop control per phase to regulate the voltage magnitude, whereas the harmonic current sharing is performed using the virtual impedance concept. Additionally, the proposed control scheme guarantees voltage regulation, causing the MG to operate at its nominal voltage value. In addition to sharing the RMS value of the current, the consensus algorithm also provides the equal sharing of the RMS value of the harmonic current between each phase of the DGs that comprise the MG and also ensures that the harmonic distortion of the voltage in the PCC of each DG remains within limits defined by the standards and recommendations. Simulation results demonstrate the functioning and effectiveness of the proposed control strategy.
Keywords: consensus algorithm; current sharing; distributed control; Microgrids; power quality